2007
DOI: 10.1074/jbc.m607482200
|View full text |Cite
|
Sign up to set email alerts
|

Cumulus Oophorus-associated Glycodelin-C Displaces Sperm-bound Glycodelin-A and -F and Stimulates Spermatozoa-Zona Pellucida Binding

Abstract: Spermatozoa have to swim through the oviduct and the cumulus oophorus before fertilization in vivo. In the oviduct, spermatozoa are exposed to glycodelin-A and -F that inhibit spermatozoa-zona pellucida binding. In this study, we determined whether these glycodelins would inhibit fertilization. The data showed that the spermatozoa without previous exposure to glycodelin-A and -F acquired glycodelin immunoreactivity during their passage through the cumulus oophorus. On the other hand, when glycodelin-A or -F-pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
53
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(55 citation statements)
references
References 70 publications
(76 reference statements)
2
53
0
Order By: Relevance
“…Thus, it was suggested that glycodelin F could help to prevent a premature acrosome reaction, before the human spermatozoa contact the zona pellucida (ZP; Yeung et al 2007). Glycodelin C, generated from glycodelins A and F in oocyte cumulus cells, has been shown to bind to sperm head, mainly in the equatorial region (Chiu et al 2007b).…”
Section: Glycodelinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it was suggested that glycodelin F could help to prevent a premature acrosome reaction, before the human spermatozoa contact the zona pellucida (ZP; Yeung et al 2007). Glycodelin C, generated from glycodelins A and F in oocyte cumulus cells, has been shown to bind to sperm head, mainly in the equatorial region (Chiu et al 2007b).…”
Section: Glycodelinsmentioning
confidence: 99%
“…Glycodelin C would remove the previously attached glycodelins A and F from spermatozoa, enhancing the zona-binding capacity of sperm passing through the cumulus oophorus (Chiu et al 2007b).…”
Section: R6 S Ghersevich and Othersmentioning
confidence: 99%
“…Hemizona binding assay was used to study the binding capability of spermatozoa to ZP as described (Chiu et al, 2007). Unfertilized human oocytes from our intracytoplasmic sperm injection program were micro-bisected into two identical hemizonae.…”
Section: Determination Of Sperm-zp Binding Capabilitymentioning
confidence: 99%
“…Several Gd isoforms with differences in glycosylation have been described: Gd-A (endometrium/decidua, amniotic fluid, and maternal serum) (Julkunen et al 1985;Dell et al 1995;Koistinen et al 2003), Gd-S (seminal vesicles and seminal plasma) (Morris et al 1996), Gd-F (follicular fluid and oviduct) (Tse et al 2002), and Gd-C (cumulus oophorus) (Chiu et al 2007).…”
mentioning
confidence: 99%